Megaliths, material engagement, and the atmospherics of neo-lithic ethics: presage for the end(s) of tourism. Issue 2 (4th March 2021) - Smith, Mick; Speiran, Siobhan; Graham, Peter
Abstract: Climate change spells the end of tourism, and tourism is just one, and one of the least important, things to be so very near its end. This situation has emerged because of the global dominance of forms of material engagement that completely misunderstand the distribution of agency in the world. Framing the world as just an external human 'resource' diminishes the many forms of agency that elude, transcend, effect, facilitate and subvert human intentions. Even archetypically inanimate objects, such as stones, are actively constitutive of worlds, thoughts, and lives, including human lives, in myriad transformative ways. This lithic agency is illustrated in terms of the attraction that draws some to visit stone circles, and the atmospheres created by, and felt in, such places. This rather different understanding of a 'visitor attraction' and its ontological and ethical implications exposes some of the inadequate presumptions of our dominant form of life and its destructive atmospheric consequences at local and global scales. The paper employs Material Engagement Theory (MET), originating in archaeology and anthropology, as a way to understand the differences between the reductive assumptions of the Anthropocene and the redemptive possibilities of what it terms a neo-lithic ethics.